ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA DRIVER OJEK ONLINE DI KOTA SEMARANG - Alviana, Rizki; Violinda, Qristin; Utami P, Ratih Hesty (Jurnal Riset Rumpun Ilmu Ekonomi, 2023)
This study aims to determine what factors affect job satisfaction of online drivers in the city of Semarang. The population used in this study were all online drivers in the city of Semarang and the sample used was 352 employees with the Slovin formula, using probability sampling technique with random sampling method. Analysis of the data in this study using the SPSS 24 program. Hypothesis testing with multiple linear regression approach. The results of the analysis and discussion show that the variables have a partial effect, namely; Welfare level has a significant positive effect on Job Satisfaction, Resilience has a significant positive effect on Job Satisfaction, Job Flexibility has a significant positive effect on Job Satisfaction, Non-Physical Work Environment has a significant positive effect on Job Satisfaction Online Drivers in Semarang City.